Pengaruh Kinerja Sektor Pertanian, Industri Dan Pariwisara Terhadap Tingkat Pengangguran Terbuka Di Provinsi Gorontalo - Daud, Riska; Arham, Muhammad Amir; Mulyati, Yenni (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the impact of the performance of the agricultural sector, industrial sector, and tourism sector in Gorontalo Province. This study uses a quantitative approach with a multiple linear regression analysis method using panel data. The data used is secondary data obtained from the Central Statistics Agency (BPS) of Gorontalo Province for the period 2020–2024. Based on GRDP data, these three sectors show a positive growth trend that supports regional economic recovery and development. The data was processed using Eviews 12. The results of the study show that partially, the performance of the agricultural, industrial, and tourism sectors has a negative effect on the open unemployment rate, which means that an increase in the performance of these three sectors can reduce the unemployment rate in Gorontalo Province. Simultaneously, these three sectors also have a significant effect on the open unemployment rate. The results of this study indicate that 1). The agricultural sector has a negative and significant effect and contributes to the open unemployment rate in Gorontalo Province, meaning that the greater the contribution of the agricultural sector, the more job opportunities are created and the more local labor can be absorbed. 2). The industrial sector has a negative and significant effect and contributes to the open unemployment rate in Gorontalo Province, meaning that the more the industrial sector develops, the more job opportunities are created that can absorb labor, both through increased production capacity and the opening of new jobs in various business fields. 3). The tourism sector has a negative and insignificant effect on the open unemployment rate in Gorontalo Province, meaning that although improvements in the performance of the tourism sector have the potential to create job opportunities, its contribution to labor absorption is still relatively small compared to the agricultural and industrial sectors, so its impact has not been significant in reducing the open unemployment rate. 4). Simultaneously, the agricultural, industrial, and tourism sectors have a significant impact on the open unemployment rate in Gorontalo Province, meaning that if these three sectors are managed and developed optimally, they can complement each other in creating new jobs, increasing regional productivity, and reducing the open unemployment rate.